2017
DOI: 10.14419/ijsw.v6i1.8677
|View full text |Cite
|
Sign up to set email alerts
|

Heritability estimates of egg weight and egg shell weight in Ikenne, Nigeria

Abstract: This study is designed to determine the inheritance pattern of egg weight and egg shell weight of exotic laying chickens at 25, 51, 72 weeks and overall mean ages of the birds. For this purpose, thirty eggs were collected daily from the birds continuously for five days of egg production, at each ages 25, 51 and 72 weeks. The total number of eggs collected at each age was 150 and 450 for the total of three age periods. The mean values of egg weight and egg shell weight revealed an apparent increase from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Overall, these estimates are in agreement with a previous study by Rath et al (2015), which reported a heritability estimate of 0.443 for the egg weight in white leghorns chickens. Furthermore, in this study, shell thickness was positively correlated with shell weight, and the estimated heritability of shell strength (0.030 in females and 0.206 in sire families) was consistent with previous reports (Rath et al, 2015; Alwell et al, 2018). For the moderate heritability of shell strength in sire family, it might be more appropriate for sire selection to achieve a quick progress in breeding.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, these estimates are in agreement with a previous study by Rath et al (2015), which reported a heritability estimate of 0.443 for the egg weight in white leghorns chickens. Furthermore, in this study, shell thickness was positively correlated with shell weight, and the estimated heritability of shell strength (0.030 in females and 0.206 in sire families) was consistent with previous reports (Rath et al, 2015; Alwell et al, 2018). For the moderate heritability of shell strength in sire family, it might be more appropriate for sire selection to achieve a quick progress in breeding.…”
Section: Discussionsupporting
confidence: 93%